Implementasi Metode Hungarian Dalam Penugasan Karyawan (Studi Kasus: PT. Jefrindo Consultant) - Oktavianus Hia (JURIKOM (Jurnal Riset Komputer), 2019)
The assignment of employees in an office is one of the things that is complicated and often has difficulty in the division of tasks which causes instability in the performance of employees. Applications using POM Qm For Windows make the process of assigning employees very easy to get results as efficiently as possible. This employee assignment problem is solved by creating an employee assignment optimization model by maximizing the level of efficiency of the use of POM Qm For Windows software to minimize the level of employee dissatisfaction with the applicable tasks. The purpose of this study is to find out the minimization of employee assignment costs that must be applied by PT. Jefrindo Consultant. In looking for minimizing the cost of machining assignments the method used is the Hungarian Algorithm to find costs that are minimal in the placement of employees. After doing the calculation results using the Hungarian method, the company should implement this method in order to minimize the cost of assigning employees to be done